Smart and innovative cities: the proposal of a framework - CÃ¢mara, Samuel Façanha (2017)
This article aims to propose a framework for developing innovative (smart) cities to developing regions. The work describes the design of the proposed framework by analyzing the characteristics of cities in Northeastern Brazil which feature a broad development space. There are important differences in their contexts that need to be analyzed for the implementation of a smart city. For this purpose it was necessary to study the characteristics of Northeastern cities and their local features. Interviews with researchers and scholars of smart cities in European countries such as Finland, the Netherlands, Spain and Portugal were performed. At last it was reviewed literature about studies on smart cities. The developed framework shows that it is possible to design an evolutionary model based on learning and the empowerment of the population, with impacts on the competitiveness of regions, the performance of their organizations and the improvement of the life quality of their citizens.JEL-Code | O18; R11; D63.